Outcomes of image-based sexual abuse among young people: a systematic review - Hellevik, Per Moum; Haugen, Linn-Eirin Aronsen; Överlien, Carolina (Frontiers in Psychology, 2025)
Image-Based Sexual Abuse (IBSA) is an increasingly recognized issue, especially among young people, yet empirical research on its consequences remains relatively scarce. Following PRISMA guidelines, a systematic search identified peer-reviewed studies published between 2010 and 2024, and eligible studies were screened and quality-assessed using standardized criteria. This systematic review synthesizes findings from 12 empirical studies to provide a comprehensive overview of the psychological, social, educational and occupational consequences of IBSA victimization among individuals aged 10–24. The findings highlight severe emotional and psychological distress, including fear, anxiety, depression, and suicidal ideation. Social repercussions such as bullying, ostracization, and victim-blaming further exacerbate these impacts. Additionally, IBSA is associated with significant disruptions in educational and occupational trajectories, with victims reporting school relocation and/or job loss. These outcomes underscore the parallels between IBSA and physical sexual abuse, emphasizing the need for targeted prevention strategies, improved legal frameworks, and informed victim support services. The study calls for further research into the long-term consequences of IBSA and the development of interventions that address both its digital and societal dimensions. Given the legal and psychological severity of IBSA, this review also highlights the need for forensic psychological assessment, integration of victim experiences into legal processes, and the development of trauma-informed policies that support young people through the justice system.